Numerical simulation on the groundwater contamination evolution in industrial settings - Bongiovanni, Marta; Tranchina, Giovanni; Torrisi, Ludovica; Mineo, Simone; Pappalardo, Giovanna (Italian journal of engineering geology and environment, 2024)
The hydrogeological numerical simulation represents a tool for the protection of aquifers and for modeling the groundwater flow and transport. This study aims to build numerical models of a porous aquifer located in the alluvial plain of Catania (eastern Sicily, Italy), to evaluate groundwater flow and hypothetical contamination plume trends, even in interaction with pumping activity. To implement the flow and transport simulations, geological and hydrogeological conceptual models were defined using borehole and well data. The studied aquifer is semi-confined, with the presence of alluvial sediments mixed with sandy clays and silts. Because of the presence of anthropic activities in the area, the accidental spill of a contaminant would represent a social problem in the frame of the environmental and health risk. In this regard, we carried out numerical simulations that consider the hydrodynamic parameters of the aquifer, the contaminant concentration, and the presence of pumping wells. The model shows that groundwater flow is directed towards east, and that the presence of wells locally affects it. The transport model shows that a hypothetical dissolved contamination plume mainly follows the groundwater flow path, and that the presence of pumping well accelerates its flow towards elements at risk.